Inovasi Kepala Sekolah Dalam Meningkatkan Keprofesionalan Tenaga Pendidik dan Kependidikan di SMAN 1 Sooko - Rosyidi, Muhammad; Yuliastuti, Lisa Aprelia; Windasari, Windasari; Hanivia Cindy, Agustin (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
This research aims to gain knowledge about Principal Innovation in Improving the Professionalism of Teachers and Education Personnel at SMAN 1 Sooko Mojokerto. The method used is a qualitative approach using several data collection methods, such as interviews, observation, literature study and analysis of relevant documents. The results of this research are to find out what the principal's strategies are for SMAN 1 Sooko in further efforts to provide encouragement and training to teaching and education staff so that the quality and professionalism of the teaching and education staff at SMAN 1 Sooko runs optimally. The welfare and professionalism of teaching and education staff at SMAN 1 Sooko has achieved a fairly good level of success. This can be seen from the increasing number of teaching and education staff who are promoted to class or rank. If welfare is improved and prioritized, it will have a big influence on the implementation of their duties. Where teaching and education staff will feel comfortable and without pressure. "Trust building, happy ending school program" The principal really builds trust through good performance, facilitating teachers and students to develop their potential, including awards or rewards for students and teaching and education staff who excel.